Predictive Ability of a Laboratory Performance Test in Mountain Bike Cross-country Olympic Athletes - Schneeweiss, Patrick; Schellhorn, Philipp; Haigis, Daniel; Niess, Andreas; Martus, Peter; Krauss, Inga (International Journal of Sports Medicine, 2019)
Mountain bike Cross-Country Olympic (XCO) has an intermittent performance profile, underlining the importance of anaerobic metabolism. Traditional performance tests in cycling primarily quantify aerobic metabolism and inadequately meet the demands in XCO. The aim was therefore to validate a specific test that quantifies these requirements by means of an XCO race.Twenty-three competitive XCO athletes (17.9±3.6 years) performed a previously developed performance test and an XCO race within one week. Correlations between individual anaerobic threshold (IAT), 4 mmol lactate threshold (LT4), maximal aerobic power (MAP), maximal effort time trials (TT) for 10–300 s and mean power output of the race (POR) were calculated. In addition, a multiple regression model of the predictive value of the test was calculated.Variables correlated significantly (p<.01) with POR: IAT (r=.81), LT4 (r=0.79), MAP (r=0.91), TT10 (r=0.75), TT30 (r=0.85), TT60 (r=0.84) and TT300 (r=0.86). In the regression model, sex and body mass were set influencing variables (R²adj.=0.70), whereby MAP had the highest correlation with POR and significantly improved the predictive value of the model (R²adj.=0.86).The high correlation of collected performance variables with POR indicated the MTB-PT’s additional benefit for performance testing in XCO because it is specific but very feasible.
Keywords: off-road cycling; performance testing; mountain biking; competition; validity; XCO